First Report of Metadelphax propinqua (Fieber) (Hemiptera: Delphacidae) Feeding on Bermudagrass in Brazil - do Prado Ribeiro L. (2024)
© Sociedade Entomológica do Brasil 2023.Bermudagrass (Cynodon dactylon (L.) Pers., Poaceae) is one of the most important pasture grasses used in milk production systems in southern Brazil, with an increasing expansion of cultivated areas in recent years. Here, we report the first occurrence of the planthopper Metadelphax propinqua (Fieber) (Hemiptera: Delphacidae) feeding on bermudagrass in Brazil. Population outbreaks of this species were observed in January/February 2023 in a commercial hay production farm in the municipality of Chapecó, Santa Catarina State, southern Brazil. Metadelphax propinqua was found in association with three cultivars of C. dactylon (Tifton 85, Jiggs, and Vaquero). The infested plants showed leaf chlorosis and a reduced plant growth rate due to sap sucking and toxin injection as well as honeydew deposition on the leaves, which led to the development of sooty mold. In addition, this delphacid species has been reported as a vector of important pathogens to bermudagrass species and other row crops. Thus, M. propinqua is a potential pest of bermudagrass in Brazil and should be monitored to assess its establishment and behavior in Brazilian pasturelands.